Selank effects on morphine-induced analgesia in vivo experiments - A. V. Nadorova; I. V. Chernyakova; L. G. Kolik (Фармакокинетика и Фармакодинамика, 2022)
Background. The endogenous opioid system is involved in neuroadaptation produced by exogenous opioids. Synthesized on the basis of the regulatory peptide tuftsin, the anxiolytic selank inhibits the activity of enkephalin-degrading enzymes, increasing the level of leu-enkephalins in blood plasma.   The aim of the work was to evaluate the effect of selank (0,3 and 0,9 mg/kg, i. p.) on morphine-induced analgesia in animal models. Methods. The experiments were performed in inbred male mice C57Bl/6 (n = 77). The “hot plate” test was used to evaluate the analgesic effect during thermal stimulation of nociceptors when mice were placed on a metal plate heated to 55 ± 0,5 °C, followed by registration of the latent period of the reaction 30, 60, 90, and 120 minutes after the administration of morphine.   Results. Morphine at a dose of 3,0 mg/kg, i. p., caused antinociception with the maximum possible effect (MBE) of 9 %, selank at a dose of 0,9 mg/kg, without antinociception per se, when pretreated with the morphine, increased the latent reaction time, causing antinociception of 29,9 % MBE.   Conclusion. For the first time the data obtained on the synergistic effect of selank and morphine in attenuation of acute somatic pain.